ANALISIS KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA DITINJAU DARI SELF-EFFICACY - Gunawan, Gunawan; Putri, Ika Septiani; Subekti, Fitrianto Eko; Kusuma, Jaka Wijaya (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2025)
Critical thinking is very important in education, especially in learning mathematics, because it is expected that students can not only solve problems, but also be able to understand and explain the thought processes underlying their solutions. One of the factors that can affect students' critical thinking ability is self-efficacy, which is a person's belief in their own ability to achieve goals. The purpose of this study is to describe students' mathematical critical thinking ability in terms of self-efficacy. This research used descriptive qualitative method. Based on the results of the self-efficacy questionnaire, researchers divided the subjects into low, medium, and high categories. Furthermore, researchers used interviews and critical thinking ability tests to collect information. To analyze the data, the researcher reduced, presented, and drew conclusions. In this study, the critical thinking process includes identifying problems/information, developing solution strategies, evaluating processes and results, and drawing conclusions. The results of this study indicate that students with high self-efficacy show better critical thinking skills compared to students with moderate and low self-efficacy. Students with high self-efficacy are not only able to identify problems well, but also develop appropriate solution strategies and evaluate results logically. Students with moderate self-efficacy have limited abilities and tend to lack confidence, although they can identify important information.